(3cJGH aj CUhd abg GdTjYIs - (3GdTjQGRj, Ydj Hf HGbQ, cGf MjG (B1234 (3g`s ((3GdeDdas)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj JYGdi Yf eWGQM GdCacGQ CeG HYO ajbhd HGbQ Hf Ydj GdTjQGRj Cfj cKjQG eG CQOJ Cf CUfa cJGHG aj CUhd Gdabg s
(3BNQgG (B:s
(3OaY GdJYGQV ajfHZj MedgG Ydi UhQI GfaQGO CMO GdWQajf HeQLM dJYGQVgG hYf EecGf GdLeY HjfgG hGddg CYde HGdUhGHs
(3ocJH HCeQ GdSdWGf ZdGe MSjfs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3CUhd Gdabgs